CHARACTER EDUCATION FROM AN EARLY AGE: FAMILY STRATEGIES IN DEVELOPING POSITIVE VALUES - Yuarini Wahyu Pertiwi; Miranu Triantoro; Dina Indriyani; Al-Amin (Adisam Publisher, 2025)
This research aims to investigate the strategies families use to develop positive values in children from an early age. This study uses a literature review where references are taken in accordance with the research context. The results showed that effective communication acts as a foundation that allows families to convey positive values, discuss the consequences of certain behaviors, and resolve value conflicts. Positive behavioral examples shown by parents were found to be the most influential factor, with children tending to imitate the behaviors they observed from their parents. Strategies of assigning responsibility and rewarding effort also contributed significantly to children's motivation to embrace positive values and apply them in their lives. Children who were given responsibility with positive support from their parents showed increased independence, confidence and willingness to contribute to their environment.